Evaluation Capacity Building and Humanitarian Organization - Ridde Valéry; Sahibullah Shakir (The Evaluation Center at Western Michigan University, 2005)
This paper documents a process of evaluation capacity building in a humanitarianorganization in Afghanistan between 2001 and 2003. The authors carried out an annual evaluation and they undertook evaluation capacity building activities. The analysis of the empirical data shows that in the context of humanitarian organizations, the capacity building process would be improved if it would i) employ a mix of participative and utilization-focused approach, ii) organize participative workshops and on-the-job training, with the continuity of collaborators ensured, iii) use a myriad of dissemination/advocacy activities for a varied public.